Test setup for analyzing the electrical resistance during fatigue loading for metastable austenite AISI 304L and its diffusion-brazed joints - Lukas M. Sauer; Johannes L. Otto; Jonas A. Ziman; Peter Starke; Frank Walther (Journal of Materials Research and Technology)
The measurement of the electrical resistance of specimens based on the established direct current potential drop (DCPD) method is a widely utilized methodology for the detection of damage mechanisms in the field of crack initiation and propagation and change in microstructural details. These include, e.g., dislocation density, void volume fraction, and micro- and macro-cracks. Given the necessity to consider additional factors influencing the electrical resistance, e.g., specimen geometry and temperature, ex-situ measurement techniques are frequently employed through interruption of fatigue testing. However, ex-situ investigations may result in unintended influences, such as changes in contacting, and analyze only discrete states limiting the characterization possibilities and result interpretation. Accordingly, in-situ electrical resistance measurements were employed in this study to characterize the microstructural changes during fatigue with cyclic creeping. To quantify and compensate the effects of geometry, temperature, and deformation-induced austenite-martensite transformation on the electrical resistance during fatigue loading, a complex experimental setup was developed which includes several measurement systems. The combination of strain measurement and potential drop enables a direct transfer of measured strain to electrical resistance. The method was applied and evaluated on high-temperature diffusion-brazed joints with a metastable austenite as base material and Ni-based filler metal. Finally, the change in microstructure was evaluated through electron channeling contrast imaging (ECCI) analyses at different load cycles.